2012
DOI: 10.1111/j.2041-210x.2012.00236.x
|View full text |Cite
|
Sign up to set email alerts
|

Temporal dynamics and network analysis

Abstract: Summary1. Network analysis is widely used in diverse fields and can be a powerful framework for studying the structure of biological systems. Temporal dynamics are a key issue for many ecological and evolutionary questions. These dynamics include both changes in network topology and flow on the network. Network analyses that ignore or do not adequately account for the temporal dynamics can result in inappropriate inferences. 2. We suggest that existing methods are currently under-utilized in many ecological an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
220
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 225 publications
(224 citation statements)
references
References 140 publications
3
220
0
1
Order By: Relevance
“…Furthermore, if acquiring a trait changes an individual's interaction patterns, then a social network constructed prior to when an individual acquired a trait might not accurately reflect its social relationships after trait acquisition. A model allowing for a dynamic network that can change over time might be more appropriate in this context (e.g., Blonder et al, 2012). New approaches are being developed that could help address some of these shortcomings; we will discuss a few of them-e.g., Markov chain models, dynamic networks-later in the review.…”
Section: Network-based Diffusion Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…Furthermore, if acquiring a trait changes an individual's interaction patterns, then a social network constructed prior to when an individual acquired a trait might not accurately reflect its social relationships after trait acquisition. A model allowing for a dynamic network that can change over time might be more appropriate in this context (e.g., Blonder et al, 2012). New approaches are being developed that could help address some of these shortcomings; we will discuss a few of them-e.g., Markov chain models, dynamic networks-later in the review.…”
Section: Network-based Diffusion Methodsmentioning
confidence: 99%
“…Despite widespread recognition of this fact, the dynamics of network topology have generally been neglected in the behavioral ecology literature (Blonder et al, 2012;Hobson et al, 2013;Pinter-Wollman et al, 2014). Most studies are based on a single, static network constructed from observed interactions and associations accumulated over some time span-i.e., a time-aggregated network.…”
Section: Dynamic Networkmentioning
confidence: 99%
See 3 more Smart Citations